RNA binding protein HuR promotes autophagosome formation by regulating expression of autophagy-related proteins 5, 12, and 16 in human hepatocellular carcinoma cells - Ji, Eunbyul; Kim, Chongtae; Kang, Hoin; Ahn, Sojin; Jung, Myeongwoo; Hong, Youlim; Tak, Hyosun; Lee, Sukchan; Kim, Wook; Lee, Eun Kyung (Molecular and Cellular Biology, 2019)
Autophagy is a process of lysosomal self-degradation of cellular components by forming autophagosomes. Autophagosome formation is an essential process in autophagy and is fine-tuned by various autophagy-related gene (ATG) products, including ATG5, ATG12, and ATG16. Although several reports have shown that numerous factors affect multiple levels of gene regulation to orchestrate cellular autophagy, the detailed mechanism of autophagosome formation still needs further investigation. In this study, we demonstrate that the RNA binding protein HuR (human antigen R) performs an essential function in autophagosome formation. We observe that HuR silencing leads to inhibition of autophagosome formation and autophagic flux in liver cells. Ribonucleoprotein immunoprecipitation (RIP) assay allows the identification of ATG5, ATG12, and ATG16 mRNAs as the direct targets of HuR. We further show that HuR mediates the translation of ATG5, ATG12, and ATG16 mRNAs by binding to their 3= untranslated regions (UTRs). In addition, we show that HuR expression positively correlates with the levels of ATG5 and ATG12 in hepatocellular carcinoma (HCC) cells. Collectively, our results suggest that HuR functions as a pivotal regulator of autophagosome formation by enhancing the translation of ATG5, ATG12, and ATG16 mRNAs and that augmented expression of HuR and ATGs may participate in the malfunction of autophagy in HCC cells.
Keywords: Autophagosomes; Autophagy; Autophagy-Related Protein 12; Autophagy-Related Protein 5; Autophagy-Related Proteins; Carcinoma, Hepatocellular; Carrier Proteins; Cell Line, Tumor; ELAV-Like Protein 1; Humans; Liver Neoplasms; Microtubule-Associated Proteins; Phagosomes; Protein Binding; RNA, Messenger; 3= UTR; RNA binding proteins; Translational control